Fatigue characteristics of dual-phase steel sheets - Onn, Irwan Herman (Korean Society of Mechanical Engineers, 2015)
Fatigue characteristics of dual-phase steel sheets, commonly used in automobile body construction were established. For this purpose, a series of fatigue tests, each at constant stress amplitude were conducted on 1.2 mm-thick, dual-phase DP600 steel sheet specimens with two different load ratios of minimum-to-maximum stress, R = 0.1 and -1. The resulting fatigue behavior is expressed in terms of fatigue strength-life (S-N) curves. Fatigue behavior of the steel sheets in the high-cycle fatigue region can be represented by Basquin’s equation with coefficient and exponent value of 921.2 and 0.093, respectively. An endurance limit of 255 MPa is observed. In addition, fatigue strengths of the dual-phase steel sheets display lower magnitude than their bulk counterparts. Effect of mean stress on fatigue behavior of the steel sheets is well predicted by Walker’s model. Exponential calibration factor is introduced to the models by SWT, Goodman and Morrow with comparable prediction to the Walker’s model